A retrospective study to assess resource utilization and costs in patients with post-stroke spasticity in the United Kingdom. (3rd July 2018) - Raluy-Callado, Mireia; Cox, Andrew; MacLachlan, Sharon; Bakheit, Abdel M.; Moore, A. Peter; Dinet, Jerome; Gabriel, Sylvie
Abstract: Objective: Post-stroke spasticity (PSS) is a common complication following stroke. This study describes the differences in healthcare resource utilization between patients who do and do not develop PSS in the UK. Methods: Adults registered in The Health Improvement Network database with a recorded stroke between 2007 and 2011 were included. PSS was identified through Read codes; machine learning was used to retrospectively identify unrecorded PSS events. Patients with diagnosed or predicted PSS in the 12 months after stroke were matched to those with no PSS on age, sex, number of strokes, socioeconomic status, and comorbidities using the nearest neighbor algorithm. Utilization and costs associated with general practitioner visits, nurse visits, hospitalizations, referrals to specialists, laboratory tests, and medications in the 12 months after stroke were compared. Results: Overall, 2, 951 PSS cases were matched to 37, 753 controls. During the first year, more PSS cases visited a physiotherapist (19% vs 7%) and occupational therapist (12% vs 5%) compared to controls. A greater proportion of cases were also referred to specialists (76% vs 64%) and hospitalized (33% vs 9%) compared to controls. Medication for spasticity was, on average, 14.68 prescriptions for cases and 5.64 for controls. Total mean costs per patient were £1, 270 (standard deviation [SD] = 772) and £635 (SD = 273) for cases and controls, respectively. Conclusion: Costs after stroke for patients developing PSS are twice as high compared to patients who do not develop it, with the major driver being the number of hospital admissions. This highlights the need for better recording and closer management of PSS.